Ritual Siraman Satu Suro di Air Terjun Sedudo Kabupaten Nganjuk Tahun 1992-2018 - Andi Jatmiko; Sugiyanto Sugiyanto; Bambang Soepeno (JURNAL HISTORICA, 2020)
The One Suro Siraman Ritual at Sedudo Waterfall is one of the traditional ceremonies performed every month Suro by the Ngliman Village people who take place at the Sedudo Waterfall tour. The main purpose of the Suro watering ceremony held at the Sedudo waterfall is as a tribute and respect for Mbah Ageng Wali Ngaliman who is considered to be the forerunner of Ngliman Village and as a thanksgiving to God for the blessings given to the people of Ngliman Village. Discussing the changes in the Suro splash ritual at Sedudo Waterfall has never changed in the core of its ritual activities because it is a tradition for the people of Ngliman Village who do not dare to change the core procession of the Suro splash ritual in the Sedudo waterfall, but the changes are seen in the transition of the waterfall manager Sedudo from the Ngliman Village Government to the Nganjuk District Government and the changes were also seen in terms of the costumes of dancers used in the splash ritual every year the costume changes were intended to attract the attention of tourists to come to see the Suro watering ritual at the Sedudo Waterfall.